Core–Shell Plasmonic Nanomaterials toward: Dual-Mode Imaging Analysis of Glutathione and Enhanced Chemodynamic Therapy - Wang, Jin; Liu, Ying-Xue; Li, Xiang-Ling; Chen, Hong-Yuan; Xu, Jing-Juan (Analytical chemistry (Washington), 2021)
A simple process, rich information, and intelligent response are the goals pursued by cancer diagnosis and treatment. Herein, we developed a core–shell plasmonic nanomaterial (Au@MnO2-DNA), which consisted of a AuNP core with an outer shell MnO2 nanosheet decorated with fluorophore modified DNA, to achieve the aforementioned aims. On the basis of the unique optical properties of plasmonic nanoparticles and the oxidability of the shell MnO2, scattering signal and fluorescence (FL) signal changes were both related to the expression level of glutathione (GSH), for which a dual-mode imaging analysis was successfully achieved on single optical microscope equipment with one-key switching. Meanwhile, the product of Mn2+ from the reaction between MnO2 and GSH not only served as a smart chemodynamic agent to initiate Fenton-like reaction for achieving chemodynamic therapy (CDT) of cancer cells but also relieved the side effect of intracellular GSH in cancer therapy. Therefore, the core–shell plasmonic nanomaterials with dual modal switching features and diagnostic properties act as excellent probes for achieving bioanalysis of aberrant levels of intracellular GSH and simultaneously activating the CDT of cancer cells based on the in situ reactions in cancer cells.